ANALISIS KINERJA TATA KELOLA TEKNOLOGI INFORMASI MENGGUNAKAN FRAMEWORK COBIT 2019 PADA UNIVERSITAS JABAL GHAFUR - Salimuddin, Salimuddin; Ula, Munirul; Nurdin, Nurdin (Universitas Lampung, 2025)
This research aims to evaluate Information Technology Governance at Jabal Ghafur University (Unigha) using the COBIT 2019 Framework. The focus of the research includes analysis of Information Technology operational processes, measurement of feasibility with the COBIT 2019 Design Factor Toolkit, and performance evaluation on two main process objectives, namely EDM03 (Ensured Risk Optimization) and MEA03 (Managed Compliance with External Requirements). This research involved respondents selected based on RACI Chart analysis, consisting of the Vice Chancellor I, Head of the General Administration Bureau, Head of the Administration Section, Head of PUKSI, Head of the Information Security Section, and Head of the Quality Assurance Agency (LPM) using a questionnaire. The analysis results show that these two process objectives have an average capability value of 100% at Capability Level 1, but only achieved Largely Achieved at Capability Level 2. The gap analysis shows a gap between the current condition (Level 1) and the desired target (Level 4), with a difference of 3. Based on these findings, it is recommended that Unigha strengthen risk management and compliance with external requirements, through updating internal policies, improving HR training and utilizing technology more effectively. This improvement is expected to increase the level of capability and performance of Information Technology Governance in Unigha.